Analisis Kebutuhan Peserta Didik Dalam Pembelajaran Biologi Sel: Dasar Pengembangan E-Modul In-VE - Rosmiati, Etty; Asmayani; Seprida, Riski (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
This study aims to describe students’ characteristics and needs in understanding Cell Biology as a basis for developing an IN-VE (Inquiry and Virtual Experiment)-based e-module. The study employed a descriptive quantitative and qualitative approach involving 25 eleventh-grade senior high school students and three biology teachers as subjects. Data were collected through a 4-point Likert scale questionnaire consisting of five dimensions—learning difficulties, motivation and interest, metacognition, learning independence, and expectations of e-module features—as well as teacher interviews. The results indicate that students’ characteristics are marked by high learning difficulties in Cell Biology (M = 3.05) and very high motivation toward the use of digital media (M = 3.53). However, their metacognitive ability (M = 2.45) and learning independence (M = 2.73) remain at a moderate level. Students’ needs point toward interactive digital learning media with very high expectations (M = 3.48), particularly regarding features such as virtual experiment simulations, inquiry-based triggering questions, self-reflection activities, automated practice questions, and multi-device access. Teacher interviews confirm that Cell Biology is a difficult topic for students and requires innovative, interactive, and flexible digital learning media. Therefore, the findings emphasize that the development of an IN-VE-based e-module is highly relevant and urgent as a solution for Cell Biology learning, not only to support conceptual understanding but also to enhance students’ metacognition and learning independence.